The Role of Office Management in Regulating Digital Information Load and Its Impact on Employee Productivity and Mental Health - Faiza Nur Muthmainah; Naila Fauzianazwa (International Journal Administration, Business & Organization, 2025)
The rapid digitization of modern work systems enhances connectivity but introduces the challenge of digital information overload, characterized by excessive message streams that disrupt concentration and psychological stability. This study examines the influence of digital communication culture on information overload and its impact on employee productivity and mental health, alongside the regulatory role of office management. Employing a Systematic Literature Review method with a descriptive-qualitative approach, this research synthesizes data from scientific literature indexed in Sinta and Scopus from 2020 to 2025 using thematic content analysis. The findings reveal that unstructured digital interaction and high message intensity correlate with increased work stress and diminished efficiency. Conversely, effective office management strategies, such as structured communication protocols and digital literacy enhancement, mitigate these negative effects while maintaining productivity and mental well-being. The study concludes that managerial intervention is crucial for designing digital communication policies that regulate information flow, ensuring technology supports rather than hinders the psychological balance of employees in hybrid and remote work environments.